Diseases in Broccoli and Their Effect on Plant Growth and Development - Erkin qizi, Yusupova Mahliyo (American Journal of Biodiversity, 2026)
This article describes the types of diseases that occur in broccoli, their biological characteristics, symptoms of diseases in broccoli and their specific aspects, the level of study of these diseases in our country, their prevalence, and scientifically based effective measures to combat them.